Dynamic-Stabilism as the Foundational Principle of Islamic Educational Ideology: A Nexus between Conservatism and Liberalism - Emas, Mahardika Putera; Taufik, H.M.; Mustain, Mustain (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2024)
This article stems from the critical importance of examining educational ideologies, including the ideology of Islamic education. Islamic educational ideology is often identified with two major streams of thought: first, liberalism, and second, conservatism. Discussions on the essence of Islamic education, for instance, ideally begin by exploring the perspectives of these two ideologies. However, both ideologies are frequently accepted as ready-made options for constructing the ideological foundation of Islamic education. Consequently, this has led to confusion, as despite certain similarities, neither liberalism nor conservatism fully aligns with all the principles and values of Islamic education. This misalignment arises from the inherent deficiencies in both ideologies. Errors in selecting or understanding the ideological foundation may result in the narrowing or distortion of the orientation of Islamic education. This paper seeks to propose an alternative foundation for Islamic educational ideology, namely Dynamic-Stabilism, as conceptualized by Wan Mohd Nor Wan Daud. The origins, development, and deficiencies of both liberalism and conservatism will be elaborated upon, followed by a comparative explanation of the Dynamic-Stabilism framework. The comparison will emphasize the points of convergence and divergence between Dynamic-Stabilism, liberalism, and conservatism. This study employs a qualitative library research method with a narrative-descriptive approach. Data will be drawn from primary sources, particularly the works of Wan Mohd Nor, as well as secondary sources that reinterpret his ideas. Based on an in-depth analysis, the findings suggest that the Dynamic-Stabilism framework is highly relevant as a foundation for achieving ideological independence in Islamic education in the future, without being constrained by the paradigms of liberalism or conservatism.Artikel ini berangkat dari pentingnya meninjau ideologi pendidikan, termasuk ideologi pendidikan Islam. Ideologi pendidikan Islam sering kali diidentifikasi dengan dua aliran pemikiran utama: pertama, liberalisme; dan kedua, konservatisme. Pembahasan mengenai esensi pendidikan Islam, idealnya, dimulai dengan menggali perspektif dari kedua ideologi ini. Namun, kedua ideologi tersebut sering diterima begitu saja sebagai pilihan yang tersedia untuk membangun fondasi ideologis pendidikan Islam. Akibatnya, hal ini sering menimbulkan kebingungan karena, meskipun terdapat beberapa kesamaan, baik liberalisme maupun konservatisme tidak sepenuhnya selaras dengan seluruh prinsip dan nilai-nilai pendidikan Islam. Ketidaksesuaian ini muncul karena adanya kekurangan yang melekat pada kedua ideologi tersebut. Kesalahan dalam memilih atau memahami fondasi ideologis dapat mengakibatkan penyempitan atau distorsi orientasi pendidikan Islam. Artikel ini bertujuan untuk mengusulkan fondasi alternatif bagi ideologi pendidikan Islam, yaitu Dynamic-Stabilism yang dikonseptualisasikan oleh Wan Mohd Nor Wan Daud. Asal-usul, perkembangan, dan kekurangan liberalisme serta konservatisme akan dijelaskan, diikuti dengan penjelasan komparatif mengenai kerangka Dynamic-Stabilism. Perbandingan ini akan menyoroti titik-titik persamaan dan perbedaan antara Dynamic-Stabilism, liberalisme, dan konservatisme. Penelitian ini menggunakan metode penelitian kepustakaan kualitatif dengan pendekatan naratif-deskriptif. Data dikumpulkan dari sumber primer, terutama karya-karya Wan Mohd Nor, serta sumber sekunder yang menafsirkan ulang gagasan-gagasannya. Berdasarkan analisis mendalam, hasil penelitian ini menunjukkan bahwa kerangka Dynamic-Stabilism sangat relevan sebagai dasar untuk mencapai kemandirian ideologis pendidikan Islam di masa depan tanpa terikat oleh paradigma liberalisme maupun konservatisme.